2020
DOI: 10.1007/s10238-020-00652-1
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a metabolic gene signature for predicting overall survival in patients with colon cancer

Abstract: The reprogramming of cellular metabolism is a hallmark of tumorigenesis. However, the prognostic value of metabolismrelated genes in colon cancer remains unclear. This study aimed to identify a metabolic gene signature to categorize colon cancer patients into high-and low-risk groups and predict prognosis. Samples from the Gene Expression Omnibus database were used as the training cohort, while samples from The Cancer Genome Atlas database were used as the validation cohort. A metabolic gene signature was esta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 39 publications
(43 reference statements)
1
19
0
Order By: Relevance
“…Wei and coworkers (12) discovered that GGT5 was highly expressed in cancer-associated fibroblasts in lung cancer, predicting the poor survival of patients with lung cancer. GGT5 was also regarded as the key metabolism-related gene in gastric cancer (28) and colon cancer (29). In our study, we found an association between high expression of GGT5 mRNA and relatively favorable progression-free survival rather than OS.…”
Section: Discussionsupporting
confidence: 53%
“…Wei and coworkers (12) discovered that GGT5 was highly expressed in cancer-associated fibroblasts in lung cancer, predicting the poor survival of patients with lung cancer. GGT5 was also regarded as the key metabolism-related gene in gastric cancer (28) and colon cancer (29). In our study, we found an association between high expression of GGT5 mRNA and relatively favorable progression-free survival rather than OS.…”
Section: Discussionsupporting
confidence: 53%
“…Recently, growing evidence has demonstrated its significant role in different carcinomas. For example, several studies have demonstrated that the overexpression of HADH was related to poor clinical outcomes in acute myeloid leukemia and colon cancer (55,56). Additionally, Shen et al illustrated that the downregulation of HADH facilitated gastric cancer cell migration and invasion through activating the Akt signaling pathway, associated with more advanced stage and poorer outcomes (57).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, growing evidence has demonstrated its significant role in different carcinomas. For example, several studies have demonstrated that the overexpression of HADH was related to poor clinical outcomes in acute myeloid leukemia and colon cancer ( 55 , 56 ). Additionally, Shen et al.…”
Section: Discussionmentioning
confidence: 99%
“…In colorectal carcinoma (CRC), expression analysis of lipid metabolism genes of patient tumor samples [ 82 ], as well as transcriptomic meta-analysis studies of CRC patient data [ 83 , 84 ], showed that the increased expression of AGPAT1 is associated with a high risk of relapse and shorter survival. Accordingly, AGPAT1 has been identified as a negative prognostic marker of CRC and was included in metabolic gene signatures that could help to classify CRC patients and be used for the development of precision therapies [ 82 , 83 , 84 ].…”
Section: The Role Of Agpats In Cancermentioning
confidence: 99%